2005
DOI: 10.1093/toxsci/kfi055
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Potentiates In Vitro Production of Proinflammatory Cytokines and Nitric Oxide by Microglia Through a Nuclear Factor kappa B-Dependent Mechanism

Abstract: Recent evidence suggests that the mechanism of manganese (Mn) neurotoxicity involves activation of microglia and/or astrocytes; as a consequence, neurons adjacent to the activated microglia may be injured. Mn modulation of proinflammatory cytokine expression by microglia has not been investigated. Therefore, the objectives of this research were to (1) assess whether Mn induces proinflammatory cytokine expression and/or modulates lipopolysaccharide (LPS)-induced expression of proinflammatory cytokines and (2) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
126
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 53 publications
19
126
0
Order By: Relevance
“…Reduction of NF-κB, ERK1/2 and JNK activation in adipose tissue of rAd-GLP-1-treated mice Activation of NF-κB is involved mainly in the expression of inflammatory responsive genes such as Il6 and Tnfa [20,21]. As pro-inflammatory cytokine production is reduced by rAd-GLP-1 treatment, we used EMSA to examine the activation of NF-κB in epididymal fat at 2 weeks after rAd-GLP-1 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of NF-κB, ERK1/2 and JNK activation in adipose tissue of rAd-GLP-1-treated mice Activation of NF-κB is involved mainly in the expression of inflammatory responsive genes such as Il6 and Tnfa [20,21]. As pro-inflammatory cytokine production is reduced by rAd-GLP-1 treatment, we used EMSA to examine the activation of NF-κB in epididymal fat at 2 weeks after rAd-GLP-1 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Mn enhances the release of inflammatory cytokines interleukin-6 and TNF-α from microglial cells (Chang and Liu 1999;Filipov et al 2005) that can promote the activation of astrocytes and subsequent release of inflammatory mediators such as prostaglandin E2 and nitric oxide (NO) Hirsch et al 1998;Spranger et al 1998). Mn also strongly potentiates NO production in cytokine-stimulated astrocytes, leading to apoptosis in co-cultured neurons Spranger et al 1998;Tjalkens et al 2008).…”
Section: Inflammatory Activation Of Gliamentioning
confidence: 99%
“…This observation is supported by studies demonstrating increased expression of NOS2 in activated astrocytes surrounding degenerating neurons in the striatum and globus pallidus of Mn-treated mice . Mn also enhances the capacity of bacterial lipopolysaccharide to promote NO production in both astroglial (Barhoumi et al 2004) and microglial (Filipov et al 2005) cells. Low concentrations of Mn can increase the capacity of TNF-α, interferon-γ, and IL-1β to induce expression of NOS2 and production of NO in astrocytes by promoting activation of the transcription factor NF-κB (Liu et al 2005;Spranger et al 1998).…”
Section: Inflammatory Activation Of Gliamentioning
confidence: 99%
“…The studies showing pretreatment with Mn++ increased survival of rats treated with endotoxin supports this idea [7]. Manganese is neurotoxic and studies have shown that it affects microgilia by increasing the production of pro-inflammatory cytokines and nitric oxide [17]. However, another example showed that Zinc pretreatment of mice attenuates TNF-α production and reduces liver injury caused by alcohol [18].…”
Section: Discussionmentioning
confidence: 98%